Related Variety, Unrelated Variety and Technological Breakthroughs: An Analysis of U.S. State-Level Patenting - Bart Los; Carolina Castaldi; Koen Frenken (European Regional Science Association (ERSA), 2013)
We investigate how variety affects the innovation output of a region. Borrowing arguments from theories of recombinant innovation, we expect that related variety will enhance innovation as related technologies are more easily recombined into a new technology. However, we also expect that unrelated variety enhances technological breakthroughs, since radical innovation often stems from connecting previously unrelated technologies opening up whole new functionalities and applications. Using patent data for US states in the period 1977-1999 and associated citation data, we find evidence for both hypotheses. Our study thus sheds a new and critical light on the related-variety hypothesis in economic geography.
Keywords: O31; R11; 330; Keywords: recombinant innovation; regional innovation; superstar patents; technological variety; evolutionary economic geography